PENGARUH PEMBERIAN INFORMASI MELALUI BROSUR DAN CERAMAH TERHADAP MINAT DONOR DARAH PEMULA DI SEKOLAH - Yulika Sugesty; Sulastri Sulastri; Renyep Proborini (Program Studi Psikologi Universitas Malahayati, 2019)
THE EFFECT OF GIVING INFORMATION THROUGH BROCHURE AND LECTURES TO BEGINNER BLOOD DONORS’ INTEREST IN SCHOOL.Introduction: In order to improve interest in blood donors, one step that can be taken is by giving information and education to change community understanding and behavior about blood donors.Purpose: This study aims to determine the effect of giving information through brochures and lectures on the interest of beginner blood donors in schools.Methods: The subjects of this study were 70 students from two classes of XI in Computer Engineering Network of Natar Budi Karya Vocational School. Interest scale was used as data collection methods and data was analyzed using the Wilcoxon test.Results: The result obtained shows there is an effect of giving information either through brochures or lectures on the interest of beginner blood donors in schools. There are differences in interest among beginner blood donors between groups given information through brochures and lectures in schoolsConclusion: Brochure found to be more effective than lectures as a media for socialization. It’s better for Lampung province UTD PMI officer to give socialization, doing a seminar, and spreading brochure about blood donors in schools so that beginner blood donors interest can be improved Pendahuluan: Untuk menumbuhkan minat donor darah, salah satu langkah yang dapat diambil adalah pemberian informasi dan edukasi dengan tujuan merubah pemahaman dan perilaku masyarakat terhadap donor darah.Tujuan: Penelitian ini bertujuan untuk mengetahui pengaruh pemberian informasi melalui brosur dan ceramah tentang minat donor darah pemula di sekolah.Metode: Subjek penelitian ini adalah 70 siswa dari dua kelas XI di Jaringan Teknik Komputer Sekolah Kejuruan Natar Budi Karya. Metode pengumpulan data menggunakan skala minat dan analisis data menggunakan uji Wilcoxon.Hasil: Hasil yang didapat menunjukkan adanya pengaruh pemberian informasi baik melalui brosur maupun melalui ceramah terhadap minat donor darah pemula di sekolah. Lebih lanjut, juga ditemukan adanya perbedaan minat donor darah pemula antara kelompok yang diberi informasi melalui brosur dan ceramah di sekolah.Simpulan: Brosur ditemukan lebih efektif daripada metode ceramah sebagai media sosialisasi. Kepada petugas UTD PMI Provinsi Lampung sebaiknya lebih banyak memberikan sosialisasi, mengadakan seminar dan penyebaran brosur di sekolah-sekolah yang bertujuan meningkatkan minat donor darah pemula di sekolah.